Vigor evaluation of six different populations of Hevea rootstocks - Gonçalves, Paulo de Souza; Martins, Antonio Lucio Mello; Bortoletto, Nelson; Ortolani, Altino Aldo; Bermond, Guilherme (Pesquisa Agropecuaria Brasileira, 1994)
This study was undertaken aiming to evaluate and to select by their vigor six different rubber tree [Hevea brasiliensis (Willd. ex. Adr. de Juss.) Well. Arg.] rootstocks, GT 1, RRIM 701, PB 235, IAN 873, RRIM 600 and unselected seedlings for a better performance of the rubber industry of São Paulo State (Brazil). For correlations the characters studied were: stem diameter (DC), height (AP), whorls number (NL) and average distance between the whorls of leaves (TL). The results of analysis of variance showed significative differences among rootstocks concerned to DC, AP and NL. The RRIM 600 rootstocks showed the least variability, and the highest was that obtained from clone PB 235, with values of 22,88% and 28,12%, respectively. The correlation values between DC and AP and DC with NL were highly significatives. The correlation coefficients values between NL and TL for all studied rootstocks were negative end highly significatives showing that as larger is the number of whorls of leaves, lesser is their size. The high correlation of DC with AP, and DC with NL, showed that it is possible to obtain vigorous rootstocks through early selection for those characters